Φρόνησις во стоичката и во епикурејската филозофија - Поповска, Јасмина (Филозофско друштво на Македонија, 2021)
Despite the change in the focus concerning ethical issues, ethics after Aristotle inherited much of his theoretical insights. Sharing the interest towards the intellectual ground of the virtues with Aristotle, Epicurus and the Stoics take φρόνησις in the center of their investigations. This article will analyze the function of φρόνησις within the ethical considerations in both schools and focus on the relations that φρόνησις has with: ἡδονή (Epicurus), φύσις and ἐπιστήμη/τέχνη (Stoics). Also, it will be considered the issues of the unity of virtues (Epicurus and Stoics) and the distinction of καθήκοντα and κατορθώματα (Stoics). In general, Hellenistic–Roman ethics does not develop around φρόνησις, although nominally φρόνησις plays a major role. It fulfils a certain important function, but its nature is easily adapted and changed depending on the ethical point that should be fulfilled, by a different author and in a different period. This leads to inconsistency in the definition of φρόνησις and confusion in its understanding